Assessment of COVID-19 response in the Republic of Korea.
The effective response of the ROK to the pandemic has been recognized worldwide. The report examines key areas of the government response efforts including testing, tracing, and treatment approaches as well as economic stimulation initiatives. The report identifies important lessons and insights for other countries to deal with the pandemic and its societal aftershocks.